Negotiating Customary Values: A Legal Anthropological Study of Social Conflict Resolution in Local Communities Amid Modernization - Eliza Meiyani; Fadhil Hayan Mochammad (Manunggal Halim Jaya, 2026)
This study examines how customary values and positive law are negotiated in the resolution of social conflicts within local communities amid ongoing processes of modernization. The objective of the research is to analyze the persistence, adaptation, and interaction of customary norms and formal legal systems from a legal anthropological perspective, while identifying the implications of such interactions for legitimacy, justice outcomes, and sustainable governance. The study employs a qualitative research approach grounded in a systematic literature review of classical and contemporary scholarship in legal anthropology, socio-legal studies, and conflict resolution. Through thematic content analysis, the research synthesizes recurring patterns, conceptual arguments, and empirical findings on legal pluralism, forum choice, and hybrid dispute-resolution mechanisms. The results indicate that modernization does not displace customary law but reshapes the conditions under which it operates, leading to negotiated and hybrid forms of legality. Customary mechanisms remain socially legitimate and effective, particularly for community-based disputes, while positive law is strategically mobilized for enforceability and external recognition. The key finding of this study is that social conflict resolution in plural legal contexts is best understood as a process of negotiated legality, in which customary values and state law are continuously reinterpreted and combined. These findings contribute to theoretical debates on legal pluralism and offer insights into the design of inclusive and sustainable conflict-resolution frameworks in modernizing societies.